Reactivity of d-fructose and d-xylose in acidic media in homogeneous phases. (29th May 2015) - Fusaro, Maxime B.; Chagnault, Vincent; Postel, Denis
Abstract: Chemistry development of renewable resources is a real challenge. Carbohydrates from biomass are complex and their use as substitutes for fossil materials remains difficult (European involvement on the incorporation of 20% raw material of plant origin in 2020). Most of the time, the transformation of these polyhydroxylated structures are carried out in acidic conditions. Recent reviews on this subject describe homogeneous catalytic transformations of pentoses, specifically toward furfural, and also the transformation of biomass-derived sugars in heterogeneous conditions. To complete these informations, the objective of this review is to give an overview of the structural variety described during the treatment of two monosaccharides (d -Fructose andd -xylose) in acidic conditions in homogeneous phases. The reaction mechanisms being not always determined with certainty, we will also provide a brief state of the art regarding this. Graphical abstract: Highlights: The reactivity ofd -Fructose andd -xylose in acidic media and in homogeneous phases. Structural variety obtained during the treatment of monosaccharides in acidic media. Brief state of the art regarding the reaction mechanisms. General schemes containing all described products are provided.